1996
DOI: 10.1152/ajplung.1996.270.3.l429
|View full text |Cite
|
Sign up to set email alerts
|

In situ activation of mouse alveolar macrophages by aerosolized liposomal IFN-gamma and muramyl tripeptide

Abstract: Interferon-gamma (IFN-gamma) was entrapped with an efficiency of 30-40% in muramyl tripeptide-containing liposomes by a freeze-thawing procedure. A microcytotoxicity assay was developed to measure the tumoricidal activity of mouse alveolar macrophages (AM) against tumoral target cells with a colorimetric viability test. Free IFN-gamma and liposomal muramyl tripeptide phosphatidylethanolamine (MTP-PE) were found to be only slightly effective to activate in vitro AM, whereas encapsulation of both INF-gamma and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Several studies demonstrated that IFN-γ synergizes with MTP-PE to increase tumoricidal activity and to induce secretion of cytokines [20,23,[28][29][30][31]. We found that MTP-PE synergizes with IFN-γ in inducing tumor killing by human macrophages, and augmenting secretion of TNF-α and IL-1β ( Fig.…”
Section: Preclinical Studies and Animal Trialsmentioning
confidence: 54%
“…Several studies demonstrated that IFN-γ synergizes with MTP-PE to increase tumoricidal activity and to induce secretion of cytokines [20,23,[28][29][30][31]. We found that MTP-PE synergizes with IFN-γ in inducing tumor killing by human macrophages, and augmenting secretion of TNF-α and IL-1β ( Fig.…”
Section: Preclinical Studies and Animal Trialsmentioning
confidence: 54%
“…If the infection were localized, it might be possible to use B30-MDP or another lipophilic derivative to localize the area of macrophage activation. Localization also increases potency of muramyl peptides as macrophage activators [49,125]. By localizing the macrophage activation, the danger of shock would be reduced.…”
Section: Limitations Of Macrophage Activationmentioning
confidence: 99%
“…MTP-PE, similarly to MDP, activates monocytes/macrophages, inducing activation of their cytotoxic function [10][11][12][13][14][15][16] and secretion of numerous cytokines, including TNF, IL-1, IL-6, IL-8, chemokine C-C motif ligand 2 (CCL2), prostaglandin E2 (PGE 2 ) and INF [9,[17][18][19][20][21][22][23]. Furthermore, L-MTP-PE induces the expression of adhesion molecules, including lymphocyte function-associated antigen (LFA)-1, intracellular adhesion molecule (ICAM)-1, and human leukocyte antigen (HLA)-DR which could be important for interaction with tumor cells [9,24].…”
Section: L-mtp-pe: a Synthetic Immune Modulator In A Liposome Drug Camentioning
confidence: 99%